To take the derivative of a constant multiple, we have our usual two steps: first, recognize the constant multiple, which means finding the constant and the function it multiplies, and applying the rule for constant multiples.
Recognize the constant multiple: Let's consider a some examples -- say, g(x) = 5 ex, h(x) = e tan(x), and p(x) = ln(a) ln(x). Are these constant multiples? Sure: for g(x), the constant 5 multiplies the function ex; for h(x), the constant e multiplies the function tan(x); and for p(x), ln(a) is a constant because a isn't a variable, so we have the function ln(x) multiplied by the constant ln(a). Then we
Apply the Rule for Constant Multiples:
z | = | c | ( f(x) ) |
z' | = | ( c | f(x) )' | |
= | c | f '(x) |
So to find the derivative of a constant multiple, we just take the derivative of the function and multiply by the constant. We show this for each of our example functions in the following table:
we start with | c | f(x) | f '(x) | final derivative | ||||
g(x) = 5 ex | 5 | ex | ex | g'(x) = 5 ex | ||||
h(x) = e tan(x) | e | tan(x) | 1 / cos2(x) | h '(x) = e / cos2(x) | ||||
p(x) = ln(a) ln(x) | ln(a) | ln(x) | 1 / x | p'(x) = ln(a) / x |